CTNI-37. REPEATED OPENING OF THE BLOOD-BRAIN BARRIER WITH THE SKULL-IMPLANTABLE SONOCLOUD-9 (SC9) DEVICE: PHASE 1 TRIAL OF NAB-PACLITAXEL AND SC9 IN RECURRENT GLIOBLASTOMA. (14th November 2022) - Sonabend, Adam M; Gould, Andrew; Luan, Yu; Hou, Ye; Kobayashi, Mikoto A; Castro, Brandyn; Zhang, Daniel Y; Chen, Li; Korobova, Farida; Amidei, Christina; Youngblood, Mark; Bebawy, John Patrick F; et al.
Abstract: BACKGROUND: The blood-brain barrier (BBB) is a major impediment to pharmacological treatment of gliomas. Low-intensity pulsed ultrasound with concomitant administration of intravenous microbubbles (LIPU/MB), temporarily opens the BBB. Here we investigate the pharmacokinetics and safety of this approach of repeated delivery of albumin-bound paclitaxel (Abraxane®, ABX) to the peri-tumoral brain. To perform LIPU/MB-based BBB opening prior to ABX infusions, we used a novel 6 x 6 cm device with 9 ultrasound emitters (SC9) that is implanted in a skull window after tumor resection. METHODS: A Phase 1 dose-escalation trial using Bayesian adaptive design was conducted (NCT04528680). Patients with recurrent operable glioblastoma, a WHO PS ≤ 2 and adequate bone marrow and organ function were eligible. After tumor resection and implantation of SC9, repeated cycles of BBB opening by LIPU/MB immediately followed by ABX, was performed every 3 weeks. Intraoperative LIPU/MB and low dose ABX was given prior to tumor resection allowed for investigation tissue concentrations and pharmacokinetics. RESULTS: Seventeen patients have been treated at six escalating ABX dose levels (40-260 mg/m 2 ). At dose of 260 mg/m 2, a grade 3 reversible taxane-associated dose limiting encephalopathy was observed in one patient. The patient continued treatment at a lower dose in subsequent cycles. A second patient exhibited encephalopathy on cycle 2. One patient developed grade 2 cumulative peripheral neuropathy. Intraoperative pharmacokinetic studies showed that ABX tissue concentrations in non-enhancing peri-tumoral brain were increased 3.7-fold after LIPU/MB. sc-RNA-sequencing showed transcriptional dysregulation of membrane transporters, pathways related to trans-cytosis as well as cell-cell and cell-matrix adhesion. CONCLUSIONS: The LIPU/MB using skull-implantable ultrasound enhances the penetration of ABX in large regions of the brain. The procedure can be performed repeatedly and safely. LIPU-based BBB opening leads to transcriptional alterations in brain endothelium. Funding: NIH/NCI 1R01CA245969-01A1, CarThera (SC9 devices), BMS/Celgene (Abraxane®).